Addressing human trafficking in the Baltic Sea Nordic-Baltic Partnership with passenger ferry companies to counter trafficking in human beings, smuggling of migrants and exploitation of migrant workers in the Baltic Sea Region - Ollus, Natalia (Publication series, 2016)
This report is part of the project “Nordic-Baltic Partnership with Passenger Ferry Companies to Encounter Trafficking in Human Beings on the Baltic Sea”. The project, launched in October 2015, is coordinated by the International Organisation for Migration (IOM), and is supported financially by the Nordic Council of Ministers and its programme against trafficking in human beings 2015-2018. The aim of the project is to advance the prevention of trafficking in human beings and to establish a dialogue with ferry companies in the Baltic Sea region with the aim of strengthening cooperation to counteract human trafficking. The findings of this research will be used to develop a set of tools for targeted training for ferry companies operating in the Baltic Sea to support them in increasing their staff awareness of trafficking in human beings and to enhance their preparedness to address trafficking in human beings to the extent possible.